Produção científica em organização do conhecimento: uma análise de domínio via cocitações de autores - Lima, Lidyane Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this research was analysis by bibliometric procedures, area field of Organization of Knowledge from the indexed publications in the journal Knowledge Organization (KO), recovered directly in the database (Scopus). The study period corresponds to the years 2004 to 2013. As theoretical and methodological foundation, we used the Domain Analysis (AD), understood as the reflection of a discourse community. The research is guided in data concerning the most productive researchers, most present themes, researchers cited a greater number of jobs, and the number of citations received, and preparation of cocitação network in order to analyze the dialogue network built by citing relative to those cited. To evaluate the dialogue between researchers and their role in different areas of science, studies and quotes cocitações are relevant procedures for examining, as contributing to the display of communicative and interactive process, as well as the underlying structure of a domain knowledge (E GRACIO OLIVEIRA, 2011). The results show a research corpus represented by articles 115 and 151 researchers (since most of the work was carried out in co-authorship) with 22 researchers were considered the most productive because they presented almost a third of the overall total of publications. Regarding the quote, 35 researchers were among the most cited, especially Hjørland, Beghtol, Olson, Svenonius, Broughton, Mai, Ranganathan, authors who presented their research on the concentration of subjects in tune with the most present themes. To prepare citation matrix and cocitação, the population of this study consists of authors who were cited (number of items) in five or more jobs. They were used Excel Software for the preparation of arrays, and Ucinet Software for the construction of cocitações network. Network indicators were calculated - density and degree of centrality - for cocitação network of authors, with the Software ...

A presente pesquisa teve como objetivo a análise, por meio de procedimentos bibliométricos, do domínio da área de Organização do Conhecimento, a partir das publicações indexadas no periódico Knowledge Organization (KO), recuperados diretamente na base de dados (Scopus). O período de estudo corresponde aos anos de 2004 a 2013. Como fundamento teórico-metodológico, utilizou-se a Análise de Domínio (A.D.), entendida como o reflexo de uma comunidade discursiva. A pesquisa está pautada no levantamento de dados relativos aos pesquisadores mais produtivos, temáticas mais presentes, pesquisadores citados em maior número de trabalhos, bem como o número de citações recebidas, e elaboração da rede de cocitação, a fim de analisar a rede de interlocução construída pelos citantes em relação aos citados. Para se avaliar a interlocução entre pesquisadores e seu papel em diferentes áreas da ciência, os estudos de citações e cocitações constituem procedimentos relevantes de análise, na medida em que contribuem para a visualização do processo comunicativo e interativo, bem como da estrutura subjacente de um domínio do conhecimento (OLIVEIRA E GRACIO, 2011). Os resultados apontam um corpus de pesquisa representado por 115 artigos e 151 pesquisadores (visto que a maioria dos trabalhos foram realizados em coautoria) sendo que 22 pesquisadores foram considerados os mais produtivos pois apresentaram quase um terço do total geral de publicações. Em relação as citações, 35 pesquisadores ficaram entre ao mais citados, destaque para Hjørland, Beghtol, Olson, Svenonius, Broughton, Mai, Ranganathan, autores que apresentaram em suas pesquisas a concentração de assuntos em sintonia com as temáticas mais presentes. Para elaboração de matriz de citação e cocitação, a população deste estudo constitui-se de autores que foram citados (em número de artigos) em cinco ou mais trabalhos. Utilizaram-se o Software...
Keywords: Bibliometria; Publicações cientificas; Ciência da informação; Cooperação intelectual; Co-autoria; Information science